Grain Boundary Phases in NbFeSb Half-Heusler Alloys: A New Avenue to Tune Transport Properties of Thermoelectric Materials - Villoro, Ruben Bueno; Zavanelli, Duncan; Jung, Chanwon; Mattlat, Dominique Alexander; Naderloo, Raana Hatami; Perez, Nicolas; Nielsch, Kornelius; Snyder, Gerald Jeffrey; Scheu, Christina; He, Ran; Zhang, Siyuan (Advanced Energy Materials, 2023)
Many thermoelectric materials benefit from complex microstructures. Grain boundaries (GBs) in nanocrystalline thermoelectrics cause desirable reduction in the thermal conductivity by scattering phonons, but often lead to unwanted loss in the electrical conductivity by scattering charge carriers. Therefore, modifying GBs to suppress their electrical resistivity plays a pivotal role in the enhancement of thermoelectric performance, zT. In this work, different characteristics of GB phases in Ti-doped NbFeSb half-Heusler compounds are revealed using a combination of scanning transmission electron microscopy and atom probe tomography. The GB phases adopt a hexagonal close-packed lattice, which is structurally distinct from the half-Heusler grains. Enrichment of Fe is found at GBs in Nb0.95Ti0.05FeSb, but accumulation of Ti dopants at GBs in Nb0.80Ti0.20FeSb, correlating to the bad and good electrical conductivity of the respective GBs. Such resistive to conductive GB phase transition opens up new design space to decouple the intertwined electronic and phononic transport in thermoelectric materials.
CRIS-Team Scopus Importer:2023-03-20
Keywords: atom probe tomography; grain boundary phase transition; half Heusler compound; thermoelectric materials; transmission electron microscopy